Improved line-of-sight nonlinear trajectory tracking control of autonomous underwater vehicle exposed to high variable speed ocean currents. (1st June 2023) - Chen, Wei; Liu, Xulin; Feng, Ziang; Tian, Yongqiang; Leng, Jianxing; Zhu, Ronghua
Abstract: In this paper, a new controller is proposed to help AUV (Autonomous Underwater Vehicle) track ideal trajectory in the high speed and variable speed ocean current environment. The kinematic and dynamic model of AUV under current interference is derived in the defined coordinate system. For the observation of variable speed current, the proposed controller proposes an improved extended state observer based on ADCP (Acoustic Doppler Current Profiler) sensor and fuzzy control. In order to resist the interference of high speed current, the proposed controller introduces an auxiliary lateral thruster to improve the anti-current capability of AUV. In order to coordinate the path tracking performance and current interference resistance of AUV, the proposed controller proposes an improved line of sight method, where observer gain is selected through fuzzy control. The improved line of sight method compensates for the prediction error of the state observer and the error in the AUV speed regulation process through the switching symbol function term in the sliding film control. The AUV's speed gradually reaches the ideal speed calculated by the navigation law through the dynamic controller, which is designed based on the backstepping method. Finally, the proposed controller is theoretically proved by the Lyapunov stability criterion and tested by comparison simulation in various working environments and controllers. Highlights: The proposed extended state observer measures the surrounding ocean flow rate and estimates the sea flow acceleration, which can effectively reduce the prediction error. And the gain parameters are picked via fuzzy control to adapt to different sampling intervals. The proposed kinematic controller chooses look-ahead distance through fuzzy control, which coordinates the resistance to current and track tracking efficiency.And the improved line of sight method designed a switching symbol function term to compensate unexpected disturbance. The proposed kinematic controller chooses look-ahead distance through fuzzy control, which coordinates the resistance to current and track tracking efficiency.And the improved line of sight method designed a switching symbol function term to compensate unexpected disturbance.